Klasszikus, bibliai és középkori reminiszcenciák Petrarca Sine nomine-leveleiben - Ertl Péter (Antikvitás és reneszánsz, 2018)
The aim of this study is to identify and analyze some classical, biblical and medieval literary reminiscences in Petrarch’s collection of satirical letters against the Papal court of Avignon, called Liber sine nomine. The examples examined illustrate how the poet combined the classical tradition with the Christian one and, thanks to the passages evoked, provided his own text with a further, political-polemical meaning. Moreover, the identification of an allusion to Virgil’s Aeneid allows a slight correction to be made to the critical text of the ninth epistle.